KONTAK PERTAMA ISLAM DENGAN FILSAFAT DAN ILMU PENGETAHUAN YUNANI - Taufik, Taufik (STIT Sunan Giri Bima, 2020)
This article argues that philoshopy and science of Greece was contributed for Islamic civilization as well as known by â€œThe Golden Ageâ€ of Muslim world history in midlle age especially, and then played an significant part in delevopment miracle of modern science in the Europe renaissance at the 15th century generally. This article will identify some of transmission related the relationship between Greeceâ€™s philoshopy and knowledge with moslems culture is considered as the success acculturation and they received it with tolerance without violence. In adittion, according to the views of scholar or historian that introduction of Muslim civilization with culture of Greece in the early period via several ways are : First, The chalipates of Islam work to expansion Islam power map so meet the central of helenism in Arab world; Second, The translation movement ideas by moslem scholars to translate Greece book philoshopy and knowledge. Third, Forum of religion debate between moslem scholars (theologists) and non Muslim theologist. The basic arguments whose used in this forum is philosophy and logica of Aristoteles. The writer of this article describes analyticcaly and critically explores the opinions of moslem scholars and theirs philoshopers about Greeceâ€™s philoshopy and knowledge. They view that it is not contradict with the Islamic values and Islam orders and stimulates his followers to learn knowledges and sciences and analyze anything by using the philoshopy thinking. Think philoshopically and rasionally is orders of Allah and his messenger and it is not prohibited by Qurâ€™an and Hadith according to QV al- Alaq : 1-5 and QV. al-Anâ€™am : 75-79.